Determinants Affecting Profitability in Insurance Companies in Indonesia - Ningsih, Shaprillia Chandra; Leon, Farah Margaretha (Jurnal Riset Akuntansi dan Keuangan, 2024)
This study aims to identify variables that affect insurance profitability in Indonesia. The addition of tangibility of asset variable as an independent variable is a novel part of this study. This research method involves collecting data from 25 insurance companies over a five-year period (2018-2022), and applying data processing analysis using panel data regression analysis techniques. The results found that underwriting risk has a negative impact on ROA, while reinsurance ratio has a negative impact on ROA. In contrast, tangibility of asset has a positive effect on ROA. Implications for financial managers to evaluate financial conditions and increase understanding of what factors can affect the profitability of insurance companies. This research also provides important information for investors in making invesments by assessing insurance copanies that have good financial performance.